The Chemokine Receptor CCR8 Is a Target of Chimeric Antigen T Cells for Treating T Cell Malignancies - Zheng, Diwei; Wang, Xindong; Cheng, Lin; Qin, Le; Jiang, Zhiwu; Zhao, Ruocong; Li, Yao; Shi, Jingxuan; Wu, Qiting; Long, Youguo; Wang, Suna; Tang, Zhaoyang; et al. (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T cells have been successfully used in the therapy of B cell leukemia and lymphoma, but still have many challenges in their use for treating T cell malignancies, such as the lack of unique tumor antigens, their limitation of T cell expansion, and the need for third party donors or genome editing. Therefore, we need to find novel targets for CAR T cell therapy to overcome these challenges. Here, we found that both adult T-cell leukemia/lymphoma (ATLL) patients and ATLL cells had increased CCR8 expression but did not express CD7. Moreover, targeting CCR8 in T cells did not impair T cell expansion in vitro. Importantly, anti-CCR8 CAR T cells exhibited antitumor effects on ATLL- and other CCR8-expressing T-ALL cells in vitro and in vivo, and prolonged the survival of ATLL and Jurkat tumor-bearing mouse models. In conclusion, these collective results show that anti-CCR8 CAR T cells possess strong antitumor activity and represent a promising therapeutic approach for ATLL and CCR8+ tumors.